CULTURAL HEALTH BELIEF AND HEALTHCARE PROVIDERS’ COMMUNICATION STRATEGIES IN TARABA STATE, NIGERIA - Suntai, Dauda Ishaya; Daniel, Hosanna Caleb (African Journal of Social and Behavioural Sciences, 2024)
This study titled “Cultural Health Belief and Healthcare Providers’ Communication Strategies in Taraba State” examined cultural beliefs and healthcare providers’ communication strategies for polio-related information in primary health centres in Jalingo. The study anchored the health belief model (HBM) to provide a framework for analysis. Both qualitative and quantitative survey designs were adopted for this study. The population comprised 213 healthcare providers in primary healthcare centres in the Jalingo Local Government Area. The findings of this study revealed that there are prevalent cultural health beliefs regarding polio vaccination, such as divine punishment, herbal emedies/traditional medicine, spiritual rituals, spiritual or supernatural beliefs, and cultural norms. The findings also showed that healthcare providers employed different communication strategies, such as training/workshops for community health workers, media campaigns/collaboration with local media outlets, community engagement events (such as health fairs, awareness walks, talkshows, and rallies), the use of religious or traditional leaders, the provision of gifts to parents/patients, house-to-house awareness campaigns, health talks, and town announcers, among others. Therefore, when healthcare providers incorporate an understanding of local cultural contexts into their communication strategies, the effectiveness of their messages on polio vaccine acceptance can improve significantly. However, stakeholders such as government and health curriculum designers should provide training and workshops for healthcare providers, particularly community health workers, to enhance their communication skills and cultural competence.